Pusa Wheat HI 8805, A high yielding durum wheat variety for timely sown, restricted irrigation conditions of Peninsular Zone of India - Ambati, Divya; Prasad, Sakuru Venkata Sai; Singh, Jang Bahadur; Phuke, Rahul Madho Rao; Prakasha, Thorehalli Linganna; Mishra, Akilesh Nandan; Sharma, Kailash Chandra; Singh, Anil Kumar; Singh, Gyanendra Pratap; Sharma, Jai Bhagwan; Singh, Pradeep Kumar; Yadav, Harikrishna; et al. (Journal of Cereal Research, 2021)
HI 8805 has average yield of 30.4 q/ha over the zone and showed significant superiority over the checks; with a potential yield of 35.4 q/ha. It has shown excellent and wider adaptation and significantly superior performance across different irrigation regimes over the checks with an average yield of 30.7q/ha. It showed high levels of field resistance to black and brown rusts. It has high protein content (12.8%), yellow pigment content (4.9 PPM), test weight (83.7 kg/hl), sedimentation value (42 ml), iron content (40.4 ppm), zinc content (33.9 ppm) with an overall pasta acceptability (5.7).